2015
DOI: 10.1136/sextrans-2014-051760
|View full text |Cite
|
Sign up to set email alerts
|

Oral and anal sex are key to sustaining gonorrhoea at endemic levels in MSM populations: a mathematical model

Abstract: Our models suggest that oral sex has an important role in sustaining gonorrhoea in a population of MSM by providing a pool of untreated asymptomatic infection. The importance of anal sex or oral sex in sustaining gonorrhoea in a heterosexual population remains uncertain due to the lack of information linking different types of sex acts and transmissibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 23 publications
(33 reference statements)
6
60
0
Order By: Relevance
“…There has been one mathematical model of gonorrhoea transmission that includes sexual activities other than penile/anal sex, and this model (2015) supports our findings 6. The model estimates that the prevalence of rectal gonorrhoea is higher among MSM with rimming (4.6%) compared with 4.1% in those who do not.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…There has been one mathematical model of gonorrhoea transmission that includes sexual activities other than penile/anal sex, and this model (2015) supports our findings 6. The model estimates that the prevalence of rectal gonorrhoea is higher among MSM with rimming (4.6%) compared with 4.1% in those who do not.…”
Section: Discussionsupporting
confidence: 79%
“…It has been widely assumed that rectal gonorrhoea is transmitted by unprotected receptive anal intercourse (RAI) 4 5. However, a recent mathematical model has shown that gonorrhoea would not be eliminated by consistent condom use during penile–anal sex as transmission can occur between other anatomical sites 6. This is consistent with a recent empirical study showing gonorrhoea positivity in MSM is increasing after adjusting for condom use during anal sex 7.…”
Section: Introductionsupporting
confidence: 63%
“…The model is an extension of a previously published model in which we examined the role of anal and oral sex in the transmission of NG in an Australian MSM population 15. The following is a brief description of the model.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to understand how gonorrhea is transmitted in order to effectively reduce the burden of this epidemic. An Australian-based mathematical model conducted by Hui et al has shown that gonorrhea cannot be eliminated even if 100% condom use is practiced for anal sex among MSM (5), suggesting that gonorrhea has other routes of transmission other than penile-anal sex. Several observational studies have shown that kissing, oroanal (rimming) practices, oral-penile sex, and saliva use as a lubricant for anal sex are all associated with the detection of gonorrhea (6,7).…”
mentioning
confidence: 99%